The past and the future display of the slide-based artwork. Slides de Cavalete (1978-1979) by Ângelo de Sousa - Silva, Joana (2021)
Slides de Cavalete (1978-1979) is a slide-based artwork by the Portuguese artist Ângelo de Sousa (1938-2011). This paper explores issues related to the exhibition of Slides de Cavalete through the view of a conservator. In the absence of the artist, the display history of this work was traced with the aim of providing a base to substantiate the decision-making process of its exhibition and preservation. Published and unpublished documentation related to the exhibitions was consulted and personalities who could have witnessed the presentation of the artwork were interviewed. During this study it was understood that Ângelo de Sousa first presented the work projected on a canvas over an easel, for the exhibition A Fotografia como Arte/A Arte como Fotografia in 1979. In the two exhibitions carried out in 2017, the work was presented as a digital projection without the use of canvas and easel. This detachment from the first presentation, might have led to a misunderstanding of the work. Based on the conducted research and following the current procedures, display options for the exhibition of Slides de Cavalete are discussed.